On the Question of the Features of Coping Mechanisms of Modern Adolescents - Pirkina, Vera Grigoryevna (Razvitie obrazovaniâ (Online), 2022)
The article is devoted to the study of the characteristics of coping mechanisms in adolescence. To overcome stress, difficult situations, coping mechanisms are formed, i. e. actions and behavioral models for resolving difficult situations. The purpose of the study is to study the characteristics of coping mechanisms in adolescents. An empirical study was conducted in 2021 on the basis of educational organizations of the Republic of Mari El and the Kirov region. The sample consisted of 667 students in grades 7–9 (322 boys and 345 girls) aged 13–15. The research method is a mass screening examination. To collect data, the E. Heim test (E. Heim), adapted in the laboratory of clinical psychology of the Psychoneurological Institute named after. V. M. Bekhterev, under the guidance of d.m.s. professor L. I. Wasserman. The results obtained showed that in order to overcome stressful situations, adolescents most often use adaptive emotional and relatively adaptive behavioral coping mechanisms, less often than others use relatively adaptive emotional coping mechanisms. Adolescent girls significantly more often than boys use maladaptive emotional and behavioral coping mechanisms. The results of the study can be useful in the development of recommendations aimed at the formation of constructive coping behavior of adolescents.